Sildenafil inhibits the growth of human colorectal cancer in vitro and in vivo - Mei, Xiao-Long (e-Century Publishing Corporation, 2015)

(untitled) (Am J Cancer Res)
Colorectal cancer is the third most common human cancer with frequent overexpression of the cGMP-specific phosphodiesterase 5 (PDE5). In the present study, we investigated that the anticancer effect of sildenafil on human colorectal cancer in vitro and in vivo, which is a potent and selective inhibitor of PDE5 for the treatment of erectile dysfunction and pulmonary arterial hypertension in the clinic. Sildenafil significantly induced cell growth inhibition, cell cycle arrest and apoptosis of human colorectal cancer with increased intracellular reactive oxidative specie (ROS) levels, which were accompanied by obvious alterations of related proteins such as CDKs, Cyclins and PARP etc. Pretreatment with ROS scavenger N-acetyl-L-cysteine could reverse sildenafil-induced ROS accumulation and cell apoptosis. Inhibition of the activity of protein kinase G with KT-5823 could enhance sildenafil-induced apoptosis. Furthermore, sildenafil caused the reduction of xenograft models of human colorectal cancer in nude mice. Overall, these findings suggest that sildenafil has the potential to be used for treatment of human colorectal cancer.